2023
DOI: 10.1002/jsfa.12818
|View full text |Cite
|
Sign up to set email alerts
|

Molecular insights into α‐glucosidase inhibition and antiglycation properties affected by the galloyl moiety in (−)‐epigallocatechin‐3‐gallate

Abstract: BACKGROUNDDiabetes mellitus poses a substantial threat to public health due to rising morbidity and mortality. α‐Glucosidase is one of the key enzymes affecting diabetes. Herein, (−)‐epigallocatechin‐3‐gallate (EGCG) and (−)‐epigallocatechin (EGC) were applied to clarify the role of the galloyl moiety of tea polyphenols in the inhibition of glycation and α‐glucosidase activity. The structure–activity relationship of the galloyl moiety in EGCG on α‐glucosidase was investigated in terms of inhibition kinetics, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…This suggested that the interactions between the complexes and ⊍-glucosidase were primarily nonfluorescent, meaning that the binding of phenolic acids and complexes to ⊍-glucosidase did not interact more strongly with tryptophan residues, tyrosine residues, and phenylalanine residues (the main sources of endogenous fluorescence of the protein). 41 This was further confirmed by the molecular docking results below. The degree of change in the secondary structure of ⊍-glucosidase was greatest in the presence of copper ions but in terms of the degree of inhibition of enzyme activity CHA-Cu was the most inhibitory.…”
Section: ⊍-Glucosidase Inhibition and In Vitro Anti-glycationsupporting
confidence: 61%
See 3 more Smart Citations
“…This suggested that the interactions between the complexes and ⊍-glucosidase were primarily nonfluorescent, meaning that the binding of phenolic acids and complexes to ⊍-glucosidase did not interact more strongly with tryptophan residues, tyrosine residues, and phenylalanine residues (the main sources of endogenous fluorescence of the protein). 41 This was further confirmed by the molecular docking results below. The degree of change in the secondary structure of ⊍-glucosidase was greatest in the presence of copper ions but in terms of the degree of inhibition of enzyme activity CHA-Cu was the most inhibitory.…”
Section: ⊍-Glucosidase Inhibition and In Vitro Anti-glycationsupporting
confidence: 61%
“…The inhibitory ability of phenolic acids was enhanced after binding to copper ions, which contradicted the result of fluorescence quenching. This suggested that the interactions between the complexes and α ‐glucosidase were primarily nonfluorescent, meaning that the binding of phenolic acids and complexes to α ‐glucosidase did not interact more strongly with tryptophan residues, tyrosine residues, and phenylalanine residues (the main sources of endogenous fluorescence of the protein) 41 . This was further confirmed by the molecular docking results below.…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Medicinal plants are rich sources of biologically active compounds with inhibitory activity against α-glucosidase (Wangkiri et al, 2021). In particular, gallic acid (Oboh et al, 2016;Choudhary et al, 2020;Xue et al, 2020;Kokila et al, 2022), theaflavin-3-gallate (Li et al, 2021) and epigallocatechin gallate ( Li et al, 2007;Xu et al, 2019;Guan et al, 2023) exhibited anti α-glucosidase activity. Consequently, it is anticipated that M01-M05 would exhibit inhibitory activity against α-glucosidase.…”
Section: α-Glucosidase Inhibitionmentioning
confidence: 99%